The Difference of Vitamin D and Calcium Levels in Preeclampsia and Normal Pregnancy - Lola Pebrianthy; Nurelilasari Siregar; Ayusdiningsih (Journal of Public Health and Pharmacy)
Background: The incidence of preeclampsia is still high in the world and in Indonesia. In obstetric care, preeclampsia still a big problem and is a cause of increasing maternal and neonatal mortality and morbidity. This research aimed to discover the difference of vitamin D and calcium level in preeclampsia and normal pregnancy.